Factors Affecting Students’ Performance in Undergraduate Exit Exams: A Systematic Review - Teshome, Samson Worku (Lembaga Yasin AlSys, 2025)
Exit examinations play a pivotal role in higher education by evaluating students’ preparedness for professional practice and maintaining academic quality. However, performance on these assessments is shaped by a complex interplay of psychological, institutional, and socio-economic factors. This systematic review investigates the determinants influencing students’ performance in exit exams across undergraduate programs. Guided by the PRISMA framework, a comprehensive literature search was conducted across major academic databases to identify peer-reviewed studies published between 1983 and 2024. Following a rigorous screening and quality appraisal process, 37 studies were included for analysis. The synthesis reveals four dominant themes influencing performance: academic preparedness, mental health status, institutional support structures, and the high-stakes nature of the assessments. Notably, high-stakes exams were consistently associated with heightened stress and test anxiety, contributing to suboptimal outcomes, while structured academic support and adequate preparation correlated positively with exam success. Additionally, socio-economic disparities and variations in institutional resources emerged as moderating variables. The review underscores the need for holistic educational strategies that balance rigorous assessment with student well-being. It recommends future longitudinal research to explore causal relationships and long-term impacts of exit examinations. The findings offer practical guidance for educators, policymakers, and academic institutions seeking to improve assessment practices and foster equitable academic outcomes in higher education.